PRODUCTION COST ANALYSIS IN DETERMINING SELLING PRICES AT PDAM TIRTA JE'NEBERANG GOWA DISTRICT - Syahreni; Muh Ilham Wardhana Haeruddin, Mustika Amin, Nurman, Annisa Paramaswary Aslam (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to determine the calculation of the basic price of PDAM Tirta Je'neberang water production, Gowa Regency in 2018-2022. The data collection techniques used in this research were interviews, decision studies, and documentation. The data analysis method used is descriptive quantitative using the full costing method calculation. The results of this research show that the cost of water production for 2018-2022 at PDAM Tirta Je'neberang, Gowa Regency, based on the full costing method theory, changes every year. This happened because of an increase in total business costs followed by an increase in the amount of water production (M3). In calculating the selling price/water tariff for PDAM Tirta Je'neberang, Gowa Regency, the basic tariff is used. It can be seen that the selling price of PDAM Tirta Je'neberang, Gowa Regency water from 2018-2022 also changes every year. Every year the cost of water production and the selling price of water change. It can be seen that the selling price is above the cost of production so that the selling price can cover the costs in full, which means the company makes a profit.